If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10x-(2x+3)=-3(1-4x)
We move all terms to the left:
10x-(2x+3)-(-3(1-4x))=0
We add all the numbers together, and all the variables
10x-(2x+3)-(-3(-4x+1))=0
We get rid of parentheses
10x-2x-(-3(-4x+1))-3=0
We calculate terms in parentheses: -(-3(-4x+1)), so:We add all the numbers together, and all the variables
-3(-4x+1)
We multiply parentheses
12x-3
Back to the equation:
-(12x-3)
8x-(12x-3)-3=0
We get rid of parentheses
8x-12x+3-3=0
We add all the numbers together, and all the variables
-4x=0
x=0/-4
x=0
| 3/n=8/32 | | 2z-20=6 | | 2x=11x+9 | | 4y-4+3y+128=180 | | 1/3(9y-24)=-17 | | 8y+6=13y-24 | | 1.4(x-12)=-3 | | 55=27+4x | | 1/3b-6=11 | | -4(x-8)=60 | | n/3-9=-4-3 | | x/2-2/3=8/3 | | 5.9=w-14 | | -12=-6x+18 | | 8(x-1)=22-5x | | 8(x-1)=5x-22 | | 8x-1=22-5x | | 2,5x-1=3x+4 | | 9g-16=56 | | 4p+22(p+5)=0 | | 0=9x^2-89x+182 | | 10x−41=4x−5 | | x/3+⅚=x/2+⅓ | | 0,5x+1=3 | | 152=20+x•12 | | 27.3=1/2(2.3+4.7)h | | —4n+66=7n | | -4+9=2n | | 2x+1÷3x-2=5÷9 | | 29.26=6g+3.94 | | -2x-5=3x-2 | | 0=9x^2-5x-210 |